1230. Epidemiology and Risk Factors for Recurrent Invasive Methicillin-Resistant Staphylococcus aureus Infection: nine US States, 2006–2013. (26th November 2018) - Kracalik, Ian; Jackson, Kelly; Nadle, Joelle; Bamberg, Wendy; Petit, Susan; Ray, Susan M; Lynfield, Ruth; Harrison, Lee H; Townes, John M; Dumyati, Ghinwa; Schaffner, William; Lake, Jason; et al.
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) causes >70, 000 invasive infections annually in the United States, and recurrent infections pose a major clinical challenge. We examined risk factors for recurrent MRSA infections. Methods: We identified patients with an initial invasive MRSA infection (isolation from a normally sterile body site) from 2006 to 2013, through active, population-based surveillance in selected counties in nine states through the Emerging Infections Program. Recurrence was defined as invasive MRSA isolation >30 days after initial isolation. We used logistic regression with backwards selection to evaluate adjusted odds ratios (aOR) associated with recurrence within 180 days, prior healthcare exposures, and initial infection type, controlling for patient demographics and comorbidities. Results: Among 24, 478 patients with invasive MRSA, 3, 976 (16%) experienced a recurrence, including 61% (2, 438) within 180 days. Risk factors for recurrence were: injection drug use (IDU) (aOR; 1.38, 95% confidence interval [CI]: 1.15–1.65), central venous catheters (aOR; 1.35, 95% CI: 1.22–1.51), dialysis (aOR; 2.00, 95% CI: 1.74–2.31), and history of MRSA colonization (aOR; 1.35, 95% CI: 1.22–1.51) (figure). Recurrence was more likely for bloodstream infections (BSI) without another infection (aOR; 2.08, 95% CI: 1.74–2.48), endocarditis (aOR; 1.46, 95% CI: 1.16–1.55), and bone/joint infections (aOR; 1.38, 95% CI: 1.20–1.59), and less likely for pneumonia (aOR: 0.75, 95% CI: 0.64–0.89), compared with other initial infection types. When assessed separately, the presence of a secondary BSI with another infection increased the odds of recurrence over that infection without a BSI (aOR: 1.96, 95% CI: 1.68–2.30). Conclusion: Approximately one in six persons with invasive MRSA infection had recurrence. We identified potential opportunities to prevent recurrence through infection control (e.g., management and early removal of central catheters). Other possible areas for preventing recurrence include improving the management of patients with BSI and bone/joint infections (including both during and after antibiotic treatment) and mitigating risk of infection from IDU. Disclosures: All authors: No reported disclosures.